Cost of a community mental health service: a retrospective study on a psychosocial care center for alcohol and drug users in São Paulo - Becker, Paula (2018)
BACKGROUND: Psychosocial care centers for alcohol and drug users (CAPS-ad) are reference services for treatment of drug users within the Brazilian National Health System. Knowledge of their total costs with- in the evidence-based decision-making process for public-resource allocation is essential. The aims here were to estimate the total costs of a CAPS-ad and the costs of packages of care (according to intensity of care); to ascertain the ratio between total CAPS-ad costs and the federal funding allocated; and to describe the methods for estimating unit costs for each CAPS-ad cost component. DESIGN AND SETTING: Retrospective study conducted in a public community mental health service. METHODS: This was a retrospective cost description study on a CAPS-ad located in a city in the state of São Paulo, using a public healthcare provider perspective and a top-down approach, conducted over a 180-day period from March 1 to August 30, 2015. RESULTS: The total mean monthly costs of the CAPS-ad were BRL 64,017.54. Healthcare staff accounted for 56.5% of total costs. The mean costs per capita and per month for intensive and non-intensive care packages were, respectively, BRL 668.34 and BRL 37.12. CONCLUSIONS: The federal budget allocation covered 62.1% of the CAPS-ad costs and the remaining 37.9% end up funded by the municipal government. The cost of the intensive package of care was 18 times greater than the non-intensive package. Developing criteria for using services and different packag- es of care based on patients’ needs, and optimizing human resources according to specific actions, may improve people’s mental health and avoid wasted resources.